Sosialisasi Penguatan Peran Masyarakat dalam Menjaga Keberlanjutan Demokrasi Berdasarkan Hukum Tata Negara - Kartika Sari, Fitri; Arqon, Mohammad; Bintang, Amar (Vox Populi: Jurnal Umum Pengabdian Kepada Masyarakat, 2025)
Sustainable democracy requires the active participation of the community in the supervision and implementation of the principles of constitutional law. In Sungai Piul, public awareness of their role in maintaining the sustainability of democracy still needs to be strengthened. Therefore, this socialization activity aims to increase public understanding of the importance of involvement in the democratic process, both through policy supervision and participation in elections and other democratic mechanisms. The method used in this activity is a qualitative approach with a descriptive-analytical method to describe the role of constitutional law in supporting community participation. The results of the socialization show that increasing public understanding of democratic principles can increase active involvement in maintaining the sustainability of democracy at the local level